2022
DOI: 10.1177/08971900221147584
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Sudden Sensorineural Hearing Loss (SSNHL) After Administration of the COVID-19 Vaccine

Abstract: Since the issuance of the emergency use authorization (EUA) of 3 coronavirus disease 2019 (COVID-19) vaccines, there have been over 180 million individuals fully vaccinated in the United States (US). With the increasing administration of COVID-19 vaccinations, there have been over 550,000 adverse events reported in the Vaccine Adverse Event Reporting System (VAERS) with approximately 230,000 experienced after receipt of the Pfizer-BioNTech COVID-19 Vaccine as of September 23rd 2021. Audio-vestibular symptoms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Regardless of the country in which the observational studies have been carried out, all authors emphasized both the low historical incidence of SSNHL and the low incidence of SSNHL after COVID-19 vaccination, as well as the need for relevant clinical data to fully explore a potential link between SSNHL and the COVID-19 vaccines. In addition to national studies conducted in the USA, Finland, Israel, France, and Denmark, we identified several case studies of SSNHL after COVID-19 vaccination [ 42 , 44 , 53 , 54 , 55 , 56 , 57 ]. Figure 1 shows the chronology of all relevant publications dealing with SSNHL after COVID-19 vaccination.…”
Section: What Do We Currently Know About Ssnhl Observed After Mrna Co...mentioning
confidence: 99%
“…Regardless of the country in which the observational studies have been carried out, all authors emphasized both the low historical incidence of SSNHL and the low incidence of SSNHL after COVID-19 vaccination, as well as the need for relevant clinical data to fully explore a potential link between SSNHL and the COVID-19 vaccines. In addition to national studies conducted in the USA, Finland, Israel, France, and Denmark, we identified several case studies of SSNHL after COVID-19 vaccination [ 42 , 44 , 53 , 54 , 55 , 56 , 57 ]. Figure 1 shows the chronology of all relevant publications dealing with SSNHL after COVID-19 vaccination.…”
Section: What Do We Currently Know About Ssnhl Observed After Mrna Co...mentioning
confidence: 99%